Evaluation of a semi-intensive husbandry system for balancing production performance and livestock welfare - Sangle Y. Randa (Jurnal Konseling dan Pendidikan, 2025)
This study explicitly aims to evaluate the effects of implementing a semi-intensive husbandry system on the balance between livestock productivity and animal welfare outcomes. The research employed a descriptive-analytical approach, collecting quantitative data on production performance (including growth trends and feed-use efficiency) and animal welfare indicators through field observations and structured interviews, along with secondary data obtained from relevant literature and technical reports. The parameters analyzed included livestock production performance, feeding management, housing environment conditions, animal health status, and animal welfare indicators. The results indicate that a semi-intensive husbandry system can improve production efficiency without neglecting livestock welfare, as reflected in stable average production performance values, controlled feeding efficiency, and a high proportion of livestock classified in good health and welfare conditions. Improvements were particularly associated with the regulation of housing duration, access to feed and water, and the provision of more adequate space for movement. However, the effectiveness of this system is strongly influenced by the quality of husbandry management and the consistent application of animal welfare standards. This study is limited by its descriptive design and site-specific scope, which may restrict the generalization of the findings. In conclusion, a semi-intensive husbandry system has the potential to serve as a sustainable husbandry model when supported by sound management practices and continuous monitoring of livestock welfare.